AMPK in regulation of apical junctions and barrier function of intestinal epithelium. Issue 2 (3rd April 2018) - Zhu, Mei-Jun; Sun, Xiaofei; Du, Min
ABSTRACT: Gut epithelium covers the inner layer of the gastrointestinal tract and provides a physical barrier to separate the host from its external environment, and its barrier function is critical for maintaining host health. AMP-activated protein kinase (AMPK) as a master regulator of energy metabolism plays a critical role in epithelial barrier function. AMPK activation promotes epithelial differentiation and facilitates cell polarity establishment, both of which strengthen epithelial barrier. In addition, AMPK promotes the assembly of tight junctions and adherens junctions by direct phosphorylation of proteins composing apical junctions, junctional anchors, and cytoskeletons. Pharmacological and nutraceutical compounds, as well as physiological states triggering AMPK activation strengthen epithelial barrier function. This review summarized recent progress in delineating the regulatory roles of AMPK in apical junction formation and barrier function of intestinal epithelium.